2012
DOI: 10.1074/jbc.m112.384669
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the HIV-1 Intasome with Transportin 3 Protein (TNPO3 or TRN-SR2)

Abstract: Background: TNPO3 is a key cellular factor involved in early steps of HIV-1 replication. Results: TNPO3 is highly structured, interacts with the HIV-1 intasome by engaging the C-terminal domain of integrase, and does not directly bind capsid tubes. Conclusion: TNPO3 interacts with HIV-1 intasomes and not capsid cores. Significance: Our findings aid future genetic analysis to elucidate the role of TNPO3 in HIV-1 replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 83 publications
4
63
0
Order By: Relevance
“…S1A). Tnpo3 is known to dimerize at high protein concentrations, and the overall shape of the observed dimers is compatible with the molecular envelope determined by small-angle X-ray scattering (43).…”
Section: Resultssupporting
confidence: 48%
“…S1A). Tnpo3 is known to dimerize at high protein concentrations, and the overall shape of the observed dimers is compatible with the molecular envelope determined by small-angle X-ray scattering (43).…”
Section: Resultssupporting
confidence: 48%
“…We previously characterized the TRN-SR2 interaction interface to identify key amino acids (27). Independent confirmation of the role of Arg 262 , Arg 263 , and Lys 264 was provided by Larue et al (38).…”
Section: Discussionmentioning
confidence: 98%
“…Although we and others have shown that TRN-SR2 directly interacts with HIV IN (18,19,27,38,39), the mechanism of action has been questioned (19,23,36,40,41). Especially reports on a set of HIV capsid mutations (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins and the Inhibitor-Full-length recombinant WT and mutant (A128T and K264A/K266A) INs containing the N-terminal His 6 tag were expressed in Escherichia coli and purified as described previously (49). Similar purification protocols were used to prepare isolated IN domains (CCD, CTD, and the CCD-CTD).…”
Section: Methodsmentioning
confidence: 99%